DESKRIPSI NILAI KARAKTER YANG TE DESKRIPSI NILAI KARAKTER YANG TERKANDUNG DALAM KOMIK CERITA RAKYAT PUTRI SERINDANG BULAN UNTUK RELEVANSI PROGRAM P5 UNTUK SISWA SEKOLAH DASAR: Indonesia - Feni Pita Winda; Abdul Muktadir; Endang Widi Winarni (UNIB Press, 2026)
This study aims to describe the character values ​​of P5 in the folklore comic Legend of Princess Serindang Bulan. This research is a Qualitative study with a descriptive method. The subject in this study is the Bengkulu folklore comic Legend of Princess Serindang Bulan. The instrument of this research is the researcher himself using the character values ​​​​table instrument and using the Validator table of each character value. The data analysis technique uses content analysis techniques. Data validity techniques through diligent observation and auditing. Based on the results of research on the character values ​​​​of P5 in the folklore comic Legend of Princess Serindang Bulan, 6 character values ​​​​were found from 6 character values ​​​​studied, meaning all P5 character values ​​​​appear in the folklore comic Legend of Princess Serindang Bulan. The 6 character values ​​​​that appear in the folklore comic Legend of Princess Serindang Bulan. namely 1) Faith, piety to God Almighty, and noble character, 2) Global Diversity Dimension, 3) Mutual Cooperation, 4) Independent Dimension, 5) Critical Reasoning Dimension and 6) Creative Dimension. These character values ​​are obtained from quotes from dialogue stories from characters in the folklore comic.